Polarizing plate with antireflection layer and image display device
By setting a transparent protective film and a water vapor barrier layer on the polarized plate, and forming an anti-reflection layer using ceramic materials, the problem of water vapor permeability caused by the anti-reflection layer is solved, and the durability and display stability of the polarized plate in high temperature and high humidity environment are achieved.
Patent Information
- Application Number
- JP2020174033
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-15
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2040-10-15
Smart Images

Figure 0007628010000002 
Figure 0007628010000003 
Figure 0007628010000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing plate with an antireflection layer, which has an antireflection layer on the surface of a polarizing plate, and an image display device. [Background technology]
[0002] Liquid crystal display devices and organic electroluminescence (EL) display devices are widely used as various image display devices such as mobile phones, car navigation devices, computer monitors, and televisions. Due to the display principle of the liquid crystal display device, a polarizing plate is arranged on the viewing side surface of the image display cell. In addition, in the case of an organic EL display device, a circular polarizing plate (a laminate of a polarizing plate and a quarter-wave plate) may be arranged on the viewing side surface of the image display cell in order to prevent external light from being reflected by the metal electrode (cathode) and being viewed as a mirror surface.
[0003] Polarizing plates generally have a transparent film on one or both sides of a polarizer for the purpose of protecting the polarizer, etc. A widely used polarizer is one in which iodine is adsorbed onto a polyvinyl alcohol (PVA) film and the molecules are oriented by stretching or the like.
[0004] When a polarizing plate is exposed to a high-temperature and high-humidity environment, the polarizer deteriorates due to moisture, causing a change in hue and a decrease in the degree of polarization. In order to prevent the deterioration of the polarizer, it has been proposed to provide a thin film having water vapor barrier properties on the surface of the polarizing plate. For example, Patent Document 1 discloses an optical laminate in which a gas barrier film is bonded to the surface of the polarizing plate via an adhesive layer. Patent Document 2 discloses a polarizer having water vapor barrier properties by forming an anti-reflection layer on a transparent film provided on the surface of the polarizer. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-134370 A [Patent Document 2] JP 2010-231160 A Summary of the Invention [Problem to be solved by the invention]
[0006] As disclosed in Patent Document 2, when an antireflection layer that also functions as a water vapor barrier layer is provided on the surface of a polarizing plate, the design of the material and film thickness of the thin film constituting the antireflection layer is limited in order to function as an antireflection layer, so it may be difficult to provide sufficient water vapor barrier properties. In addition, since the antireflection layer is disposed on the outermost surface of the image display device, it is prone to being scratched in the environment in which the image display device is used. Even if the antireflection layer has excellent water vapor barrier properties, if the antireflection layer is scratched, moisture is likely to penetrate into the polarizing plate through the scratched portion, and when the antireflection layer is exposed to a high-temperature and high-humidity environment, display unevenness due to localized deterioration of the polarizer may occur.
[0007] In view of the above, an object of the present invention is to provide a polarizing plate with an antireflection layer, which has excellent durability and is less susceptible to deterioration of the polarizer even when exposed to a high-temperature and high-humidity environment. [Means for solving the problem]
[0008] The polarizing plate with an antireflection layer comprises a polarizing plate, an antireflection film, and an adhesive layer. The polarizing plate comprises a polarizer and a first transparent protective film attached to a first main surface of the polarizer, and a water vapor barrier layer is provided on the first main surface of the first transparent protective film. A second transparent protective film may be attached to the second main surface of the polarizer. The antireflection film comprises an antireflection layer on the first main surface of a transparent film substrate. In the polarizing plate with an antireflection layer, the water vapor barrier layer of the polarizing plate and the transparent film substrate of the antireflection film are attached to each other via an adhesive layer.
[0009] The hygroscopic expansion coefficient of the first transparent protective film of the polarizing plate is preferably 0.10% or less. The arithmetic mean height Sa of the first main surface (the surface on which the water vapor barrier layer is formed) of the first transparent protective film is preferably 1.5 nm or less. The first transparent protective film may have a smoothing coating layer on the first main surface of the transparent film.
[0010] The water vapor barrier layer has a moisture permeability of 1g / m 2 - 24h or less, 0.5g / m 2 24 hours or less is preferable. The material of the water vapor barrier layer is preferably a ceramic material made of an oxide, nitride, or oxynitride of a metal or semimetal element such as Si, Al, In, Sn, Zn, Ti, Nb, Ce, or Zr. The water vapor barrier layer is preferably a sputtered film formed by a sputtering method.
[0011] The transparent film substrate of the anti-reflection film may have a hard coat layer on the surface of the transparent film. The anti-reflection film may have a primer layer between the transparent film substrate and the anti-reflection layer. The anti-reflection layer is preferably a laminate of a plurality of thin films having different refractive indices. The thin film constituting the anti-reflection layer is a sputtered film formed by a sputtering method. An antifouling layer may be provided on the anti-reflection layer.
[0012] The interface reflectance between the water vapor barrier layer and the pressure-sensitive adhesive layer is preferably 1% or less. For example, the interface reflectance can be reduced by adjusting the material and thickness of the water vapor barrier layer. Effect of the Invention
[0013] The polarizing plate with an antireflection layer of the present invention has excellent durability and is unlikely to deteriorate due to the intrusion of moisture into the polarizer even when exposed to a high-temperature and high-humidity environment. Even if the antireflection layer is scratched, the intrusion of moisture into the polarizer is suppressed, so that even in the use environment of an image display device, deterioration of display characteristics and display unevenness due to the deterioration of the polarizer are unlikely to occur, and the polarizing plate has excellent durability. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is a cross-sectional view showing a lamination form of a polarizing plate with an antireflection layer. [Diagram 2] FIG. 1 is a cross-sectional view showing a lamination configuration of an image display device having a polarizing plate with an antireflection layer on the viewing side surface of an image display medium. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] 1 is a cross-sectional view showing an example of the laminated structure of a polarizing plate with an antireflection layer, and Fig. 2 is a cross-sectional view showing an example of the laminated structure of an image display device including a polarizing plate 200 with an antireflection layer on an image display medium 110. In the polarizing plate 200 with an antireflection layer, an antireflection film 105 is bonded to a first main surface of a polarizing plate 101 via an adhesive layer 8. In the following, the main surface on the upper side (antireflection film 105 side) of each layer in the figure will be referred to as the "first main surface", and the main surface on the lower side (polarizing plate 101 side) will be referred to as the "second main surface".
[0016] In the polarizing plate 101, a first transparent protective film 2 is bonded to a first main surface of a polarizer 1, and a water vapor barrier layer 3 is provided on the first main surface of the first transparent protective film 2. A second transparent protective film 15 may be bonded to a second main surface of the polarizer 1. A pressure-sensitive adhesive layer 9 for bonding to an image display medium 110 may be laminated on the second main surface of the polarizing plate 101.
[0017] The antireflection film 105 includes an antireflection layer 5 on a first main surface of a transparent film substrate 4. A primer layer 50 may be provided between the transparent film substrate 4 and the antireflection layer 5. An antifouling layer 6 may be provided on the first main surface of the antireflection layer 5.
[0018] [Polarizing plate with water vapor barrier layer] <Polarizer> Examples of the polarizer 1 include hydrophilic polymer films such as polyvinyl alcohol films, partially formalized polyvinyl alcohol films, and partially saponified ethylene-vinyl acetate copolymer films, which are uniaxially stretched after adsorbing a dichroic substance such as iodine or a dichroic dye, and polyene-based oriented films such as dehydrated polyvinyl alcohol and dehydrochlorinated polyvinyl chloride.
[0019] Among them, a polyvinyl alcohol (PVA)-based polarizer in which a dichroic substance such as iodine or a dichroic dye is adsorbed on a polyvinyl alcohol or a partially formalized polyvinyl alcohol film and aligned in a predetermined direction is preferred because it has a high polarization degree. For example, a PVA-based polarizer can be obtained by dyeing a PVA-based film with iodine and stretching it.
[0020] The thickness of the polarizer is, for example, about 2 to 50 μm. A thin polarizer can also be used as the polarizer. For example, a thin PVA-based polarizer can be obtained by a manufacturing method including a step of stretching a PVA-based resin layer and a resin substrate for stretching in a laminate state and a step of dyeing with iodine. The thickness of the polarizer may be 20 μm or less, 15 μm or less, 10 μm or less, or 8 μm or less.
[0021] <Transparent protective film> A transparent protective film 2 is attached to a first main surface of the polarizer 1 via an adhesive layer (not shown). The transparent protective film 2 has a visible light transmittance of preferably 80% or more, and more preferably 90% or more. The transparent protective film 2 may include a coating layer 22 on a transparent film 21.
[0022] The transparent protective film 2 disposed on the first main surface of the polarizer 1 functions not only as a polarizer protective film but also as a base layer for the water vapor barrier layer 3. The transparent protective film 2 preferably has a small coefficient of moisture expansion. The coefficient of moisture expansion is the rate of dimensional change of the film after it is left to stand for 72 hours in an environment at a temperature of 65°C and a relative humidity of 90%.
[0023] Since the transparent protective film 2 has a small hygroscopic expansion coefficient, cracks are unlikely to occur in the barrier layer 3 even when the polarizing plate is exposed to a high-temperature and high-humidity environment, and deterioration of the polarizer 1 caused by moisture (mainly yellowing) tends to be suppressed. The hygroscopic expansion coefficient of the transparent protective film 2 is preferably 0.10% or less, more preferably 0.08% or less. The hygroscopic expansion coefficient may be 0.06% or less or 0.05% or less. The hygroscopic expansion coefficient of the transparent protective film 2 may be a negative value (the dimensions are reduced by hygroscopicity). If the hygroscopic expansion coefficient is excessively small (the shrinkage coefficient is large), appearance defects such as color unevenness due to stress at the interface with the polarizer are likely to occur. Therefore, the hygroscopic expansion coefficient of the transparent protective film is preferably -0.20% or more, more preferably -0.15% or more, and even more preferably -0.10% or more.
[0024] The transparent protective film 2 may have anisotropy in the moisture absorption expansion coefficient. For example, a film produced by a roll-to-roll process may have anisotropy in the machine direction (MD) and the transverse direction (TD). A stretched film may have anisotropy in the stretching direction and the direction perpendicular to the stretching direction. When the transparent protective film 2 has anisotropy in the moisture absorption expansion coefficient, it is sufficient that the moisture absorption expansion coefficient in either one of the directions is within the above range. It is preferable that both the moisture absorption expansion coefficients in the MD and TD are within the above range.
[0025] The transparent film 21 is preferably one that is excellent in transparency and heat resistance and has a small coefficient of moisture expansion. In general, the smaller the moisture absorption coefficient of a material, the smaller the coefficient of moisture expansion tends to be. Examples of resin materials constituting the transparent film 21 include (meth)acrylic resins, polyesters such as polyethylene terephthalate (PET), polyolefins, cyclic polyolefins (polynorbornene), polycarbonates, polyethersulfones, polysulfones, polystyrenes, and the like. As the (meth)acrylic resin, a (meth)acrylic resin having a lactone ring structure or a (meth)acrylic resin having an unsaturated carboxylic acid alkyl ester unit and a glutarimide unit may be used.
[0026] The thickness of the transparent protective film 2 is not particularly limited, but is preferably about 5 to 300 μm, more preferably 10 to 300 μm, and even more preferably 20 to 200 μm, from the viewpoints of strength, workability such as handleability, thin layer property, etc. When the transparent protective film 2 has a coating layer 22 on the surface of the transparent film 21, the thickness including the coating layer 22 is preferably within the above range.
[0027] The first main surface of the transparent protective film 2 (the surface on which the barrier layer 3 is formed) is preferably smooth with few surface irregularities. If the first main surface of the transparent protective film 2 is smooth, the water vapor barrier property of the water vapor barrier layer 3 formed thereon tends to be enhanced and the moisture permeability tends to be reduced. The arithmetic mean height Sa of the first main surface of the transparent protective film 2 is preferably 1.5 nm or less, more preferably 1.2 nm or less, and even more preferably 1.0 nm or less. The arithmetic mean height Sa may be 0.8 nm or less, 0.6 nm or less, or 0.5 nm or less. The arithmetic mean height Sa is calculated in accordance with ISO 25178 from the three-dimensional surface shape within an area of 1 μm×1 μm measured by an atomic force microscope (AFM).
[0028] The arithmetic mean height Sa of the transparent protective film 2 can also be reduced by providing a coating layer 22 having a smoothing effect on the surface of the transparent film 21. The coating layer 22 for smoothing the surface is preferably formed by wet coating. Since the wet coating reduces the surface irregularities of the transparent film 21, the arithmetic mean height Sa tends to be reduced.
[0029] The thickness of the coating layer 22 is not particularly limited. The thicker the coating layer, the smoother the surface tends to be. The thickness of the coating layer 22 provided to smooth the surface is preferably 0.5 μm or more, more preferably 1 μm or more. The thickness of the coating layer 22 may be 10 μm or less, 7 μm or less, or 5 μm or less.
[0030] The coating layer 22 may be a hard coat layer (cured resin layer). In a polarizing plate with an antireflection layer, the water vapor barrier layer 3 provided on the coating layer 22 is attached to the adhesive layer 8 and is not exposed on the surface, so there is no need to increase the hardness. Therefore, the coating layer 22 does not necessarily have to be a hard coat layer, and may be a coating layer of a resin solution that does not have curing properties. In addition, when the transparent film 21 has high smoothness, the coating layer 22 does not need to be provided.
[0031] A second transparent protective film 15 may be attached to the second main surface of the polarizer 1. The thickness and material of the second transparent protective film 15 are not particularly limited and may be the same as those described above for the thickness and material of the first transparent protective film 2. The material of the second transparent protective film 15 may be the same as that of the first transparent protective film. The second transparent protective film 15 is not required to have smoothness or low hygroscopic expansion properties like the first transparent protective film 2 that serves as a base for the barrier layer 3. Therefore, a highly water-absorbent material such as a cellulose-based material may be used as the material of the second transparent protective film.
[0032] The second transparent protective film 15 may also function as a retardation plate. The second transparent protective film 15 may be a laminate of two or more films, or may be a laminated retardation plate. The second transparent protective film may be a transparent film having a birefringent layer such as an aligned liquid crystal layer provided thereon.
[0033] An adhesive is preferably used to bond the polarizer 1 and the transparent protective films 2 and 15. Examples of adhesive materials include epoxy resins, silicone resins, acrylic resins, polyurethane, polyamide, polyether, and polyvinyl alcohol. The thickness of the adhesive layer is, for example, about 0.01 to 10 μm. When a curing adhesive that exhibits adhesiveness through a crosslinking reaction is used, the thickness of the adhesive layer is preferably 0.01 to 5 μm, and more preferably 0.03 to 3 μm.
[0034] The adhesive may be in various forms, such as a water-based adhesive, a solvent-based adhesive, a hot melt adhesive, or an active energy ray curable adhesive. Of these, water-based adhesives or active energy ray curable adhesives are preferred because they can reduce the thickness of the adhesive layer. Examples of the polymer component of the water-based adhesive include vinyl polymer, gelatin, vinyl latex, polyurethane, polyester, and epoxy. The active energy ray curable adhesive is an adhesive that can be radically polymerized, cationic polymerized, or anionically polymerized by irradiation with active energy rays such as electron beams or ultraviolet rays. Of these, photoradical polymerizable adhesives, photocationic polymerizable adhesives, or hybrid adhesives that use both photocationic polymerization and photoradical polymerization, are preferred because they can be cured with low energy. Examples of monomers for radical polymerizable adhesives include compounds having a (meth)acryloyl group and compounds having a vinyl group.
[0035] <Water vapor barrier layer> The first main surface of the transparent protective film 2 is provided with a moisture permeability of 1 g / m 2 The water vapor barrier layer 3 has a moisture permeability of 0.5 g / m2 or less. The provision of the water vapor barrier layer (hereinafter sometimes referred to as the "barrier layer") prevents moisture in the air from penetrating into the polarizer 1, so that yellowing due to deterioration of the polarizer can be prevented even if the polarizing plate is exposed to a high-temperature and high-humidity environment. The moisture permeability of the barrier layer 3 is 0.5 g / m2 or less. 2 24 hours or less is preferable, 0.3g / m 2 24h or less is more preferable, 0.2 / m 2 From the viewpoint of preventing deterioration of the polarizer, the smaller the moisture permeability of the barrier layer 3, the more preferable. The lower limit of the moisture permeability of the barrier layer 3 is not particularly limited, but is generally 1.0×10 -4 g / m 2 From the viewpoint of releasing outgassing from the transparent protective film 2, etc., the moisture permeability of the barrier layer 3 is 1.0× -3 g / m 2 24 hours or more is preferable.
[0036] The moisture permeability is measured according to Appendix B of JIS K 7129:2008 (Mocon method) under conditions of a temperature of 40°C and a relative humidity difference of 90%. Note that the barrier layer 3 is a thin film, and it is difficult to measure the moisture permeability of the barrier layer 3 alone. Therefore, the moisture permeability of a laminate in which the barrier layer 3 is provided on the transparent protective film 2 is regarded as the moisture permeability of the barrier layer 3. The moisture permeability of a polarizing plate 101 in which the barrier layer 3 is provided on the transparent protective film 2 may also be regarded as the moisture permeability of the barrier layer 3. The polarizer 1 and the transparent protective films 2 and 15 are made of resin materials and have sufficiently higher moisture permeability than the water vapor barrier layer 3, so that the moisture permeability of a laminate in which the barrier layer 3 is provided on these films can be regarded as being equal to the moisture permeability of the barrier layer 3 alone.
[0037] The material of the barrier layer 3 is not particularly limited as long as it exhibits the above moisture permeability, but is preferably an inorganic thin film, and is preferably a ceramic material such as an oxide, nitride, or oxynitride of a metal or semimetal. In particular, an oxide, nitride, or oxynitride of Si, Al, In, Sn, Zn, Ti, Nb, Ce, or Zr is preferable because it has both low moisture permeability and transparency. The barrier layer 3 may be a ceramic material containing a plurality of (semi)metal elements. Among these, silicon oxide, silicon oxynitride, silicon nitride, and aluminum oxide are preferable. The barrier layer may have a laminated structure of two or more layers.
[0038] The thickness of the barrier layer 3 is not particularly limited. From the viewpoint of improving the water vapor barrier property, the thickness of the barrier layer 3 is preferably large. On the other hand, if the thickness of the barrier layer 3 is excessively large, it may cause cracks, a decrease in production efficiency, and an increase in costs. The thickness of the barrier layer 3 is, for example, 10 to 300 nm, preferably 20 to 250 nm, more preferably 30 to 200 nm, and further preferably 40 to 150 nm.
[0039] The barrier layer 3 may be a single layer film consisting of only one layer, or a multilayer film consisting of two or more layers. When the barrier layer 3 is a multilayer film, by appropriately selecting the lamination structure (number of layers, refractive index and film thickness of each layer), the barrier layer 3 can function as an optical interference layer to reduce reflection at the interface between the pressure-sensitive adhesive layer 8 and the barrier layer 3 and at the interface between the barrier layer 3 and the transparent protective film 2. An example of the barrier layer of the multilayer film is a lamination structure consisting of a high refractive index layer having a refractive index of about 1.8 to 2.5 and a low refractive index layer having a refractive index of about 1.3 to 1.5.
[0040] The barrier layer 3 may include a primer layer in contact with the transparent protective film 2. The primer layer has a function of increasing the adhesion of the barrier layer to the transparent protective film 2, and similarly to the primer layer 50 described below, a metal, a metal oxide, a fluoride, a sulfide, a nitride, or the like is used.
[0041] The barrier layer 3 may be formed on the transparent protective film 2 before bonding the transparent protective film 2 to the polarizer 1, or may be formed after bonding the transparent protective film 2 and the polarizer 1 to form a polarizing plate. When the transparent protective film 2 and the polarizer 1 are bonded together using a water-based adhesive, it is preferable to form the barrier layer 3 on the transparent protective film after bonding the polarizer 2 and the transparent protective film 2 together, from the viewpoint of suppressing poor appearance such as poor adhesion and unevenness caused by retention of moisture at the bonding interface.
[0042] The method for forming the barrier layer 3 is not particularly limited, and may be a dry coating method or a wet coating method. Dry processes such as sputtering, ion plating, vacuum deposition, and CVD are preferred because they tend to form a film with high film density and high water vapor barrier properties, and among them, sputtering is preferred because it is capable of forming a dense film.
[0043] In the sputtering method, a thin film can be continuously formed while a long film is transported in one direction (longitudinal direction) by a roll-to-roll method. This can improve the productivity of polarizing plates with a barrier layer. In the sputtering method, the film is formed while an inert gas such as argon and, if necessary, a reactive gas such as oxygen are introduced into a chamber. The formation of an oxide layer by the sputtering method can be carried out by either a method using an oxide target or reactive sputtering using a metal target. In order to form a metal oxide film at a high rate, reactive sputtering using a metal target is preferred. When forming a nitride or oxynitride, the film may be formed while introducing nitrogen gas.
[0044] In sputtering deposition, it is preferable to control the substrate temperature in the range of -20 to 180°C. By increasing the substrate temperature, a dense film is easily formed and the moisture permeability of the barrier layer tends to decrease. On the other hand, if the substrate temperature is excessively high, it may cause poor running of the film or wrinkles.
[0045] When forming a silicon-based ceramic layer such as silicon oxide, silicon nitride, or silicon oxynitride by sputtering, in addition to sputtering gas such as argon, reactive gas such as oxygen or nitrogen, a gas with a water pressure of 1.0×10 -4 ~1.0×10 -2 It is preferable to perform the film formation while introducing water so that the pressure is in the range of about Pa. The film formation pressure in the sputtering film formation is about 0.05 to 1 Pa, and preferably about 0.1 to 0.5 Pa.
[0046] As described above, by forming a thin film on the transparent protective film 2 having little surface irregularity and a small arithmetic mean height Sa, it is easy to form the barrier layer 3 with low moisture permeability. Furthermore, by forming the barrier layer 3 on the transparent protective film 2 having a small moisture absorption expansion coefficient, cracks are unlikely to occur in the barrier layer 3 even when the polarizing plate is exposed to a high-temperature and high-humidity environment, and moisture-induced deterioration (mainly yellowing) of the polarizer 1 tends to be suppressed.
[0047] [Anti-reflective film] The antireflection film 105 includes an antireflection layer 5 on a first main surface of a transparent film substrate 4, optionally via a primer layer 50. The antireflection layer is a laminate of two or more thin films, and FIG. 1 illustrates an antireflection layer 5 consisting of a laminate of four thin films 51, 52, 53, and 54.
[0048] <Transparent film substrate> The transparent film substrate 4 includes a transparent film 41. A hard coat layer 42 is preferably provided on a first main surface of the transparent film 41 (the surface on which the antireflection layer 5 is formed).
[0049] The transparent film substrate 4 has a visible light transmittance of preferably 80% or more, more preferably 90% or more. The thickness of the transparent film substrate 4 is not particularly limited, but from the viewpoints of strength, workability such as handleability, thin layer property, etc., it is preferably about 5 to 200 μm, more preferably 10 to 150 μm, and even more preferably 40 to 100 μm.
[0050] The resin material constituting the transparent film 41 is preferably the same as that described above as the material of the transparent protective film. In the polarizing plate with an antireflection layer, the barrier layer 3 is provided on the transparent protective film 2 of the polarizing plate 101, thereby suppressing the deterioration of the polarizer caused by the intrusion of moisture. Therefore, the antireflection film does not need to have water vapor barrier properties, and the transparent film 41 is not required to be smooth. In addition, the transparent film 41 is bonded to the barrier layer 3 via the adhesive layer 8, and even if the transparent film 41 changes in size due to moisture absorption and expansion, the stress at the interface is alleviated, so low moisture absorption and expansion properties are not required. Therefore, the transparent film 41 may be made of a material with high moisture absorption, such as a cellulose-based resin (e.g., triacetyl cellulose).
[0051] A hard coat layer 42 is preferably provided on the surface of the transparent film 41. By providing the hard coat layer 42 on the surface of the transparent film substrate 4 on which the antireflection layer 5 is formed, the mechanical properties such as hardness and elastic modulus of the antireflection layer 5 can be improved. The hard coat layer 42 preferably has high surface hardness and excellent scratch resistance. The hard coat layer 42 can be formed, for example, by applying a solution containing a curable resin onto the transparent film 41. When a curable resin is used, it is preferable to cure the resin by heating or irradiation with active light after application.
[0052] Examples of the curable resin include thermosetting resin, ultraviolet curing resin, and electron beam curing resin. Examples of the type of curable resin include various resins such as polyester, acrylic, urethane, acryl urethane, amide, silicone, silicate, epoxy, melamine, oxetane, and acryl urethane. Among these, acrylic resin, acryl urethane resin, and epoxy resin are preferred because they have high hardness, can be cured with ultraviolet light, and have excellent productivity, and among these, acryl urethane resin is preferred.
[0053] The hard coat layer 42 may contain fine particles. For example, by including fine particles in the hard coat layer, unevenness may be formed on the surface of the hard coat layer 42, thereby imparting antiglare properties. The fine particles used to impart antiglare properties are preferably microparticles having a particle size on the order of μm. The average particle size of the microparticles is preferably 0.5 to 10 μm, and more preferably 1 to 5 μm.
[0054] The formation of fine irregularities on the surface of the hard coat layer 42 tends to improve adhesion with the antireflection layer 5 (or primer layer 50) provided thereon. The fine particles used to form irregularities on the surface of the hard coat layer 42 that provide excellent adhesion with thin films such as the primer layer 50 and the antireflection layer 5 are preferably nanoparticles having a particle size on the order of nm. The average particle size of the nanoparticles is preferably 10 to 150 nm, more preferably 20 to 100 nm, and even more preferably 25 to 80 nm.
[0055] The shape of the fine particles is not particularly limited, but is preferably a (near) spherical shape with an aspect ratio of 1.5 or less. The aspect ratio of the particles is more preferably 1.2 or less, and even more preferably 1.1 or less. The content of the fine particles in the hard coat layer is about 1 to 60% by weight, and may be adjusted depending on the type of fine particles and the purpose of addition.
[0056] As the fine particles, various metal oxide fine particles such as silica, alumina, titania, zirconia, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide; glass fine particles; crosslinked or uncrosslinked organic fine particles made of various transparent polymers such as polymethyl methacrylate, polystyrene, polyurethane, acrylic-styrene copolymer, benzoguanamine, melamine, and polycarbonate; silicone fine particles, and other transparent fine particles can be used without any particular limitation. As the nanofine particles, inorganic oxides are preferred. Functional groups such as acrylic groups and epoxy groups may be introduced on the surface of the inorganic oxide particles in order to increase the adhesion and affinity with resins.
[0057] The thickness of the hard coat layer 42 is not particularly limited, but in order to achieve high hardness, the thickness is preferably 1 μm or more, more preferably 1.5 μm or more, and even more preferably 2 μm or more. In consideration of the ease of formation by coating, the thickness of the hard coat layer is preferably 15 μm or less, more preferably 10 μm or less, and even more preferably 8 μm or less.
[0058] The surface of the transparent film substrate 4 may be subjected to a surface modification treatment such as corona treatment, plasma treatment, frame treatment, ozone treatment, primer treatment, glow treatment, saponification treatment, or treatment with a coupling agent for the purpose of improving adhesion to the antireflection layer 5. For example, by carrying out a plasma treatment in a vacuum, the surface of the substrate is modified and appropriate irregularities are formed on the surface, which tends to improve adhesion between the transparent film substrate 4 (hard coat layer 42) and the antireflection layer 5 (or primer layer 50).
[0059] As described above, in a polarizing plate with an antireflection layer, it is not necessary for the antireflection layer 5 to have water vapor barrier properties, so that unevenness may be provided on the surface of the transparent film substrate 4 that serves as the base for the antireflection layer 5. Therefore, the arithmetic mean height of the second main surface of the transparent film substrate 4 may be greater than the arithmetic mean height of the first main surface of the transparent protective film 2. When the arithmetic mean height Sa of the first main surface of the transparent film substrate 4 is large, the adhesion of the antireflection layer 5 to the transparent film substrate 4 tends to be improved.
[0060] From the viewpoint of improving the adhesion of the anti-reflection layer 5 (and the primer layer 50), the arithmetic mean height Sa of the first main surface of the transparent film substrate 4 is preferably 1.5 nm or more. The arithmetic mean height Sa of the first main surface of the transparent film substrate 4 may be 2 nm or more, 2.5 nm or more, or 3 nm or more. On the other hand, if the surface unevenness becomes coarse, sufficient adhesion may not be realized. Therefore, the arithmetic mean height Sa of the first main surface of the transparent film substrate 4 is preferably 8 nm or less, more preferably 7.5 nm or less, and even more preferably 7 nm or less. The uneven shape of the surface of the hard coat layer 42 can be adjusted by adjusting the particle size and content of the fine particles (particularly nanoparticles). In addition, the arithmetic mean height Sa of the first main surface of the hard coat layer 42 can also be increased by dry etching such as plasma treatment.
[0061] <Primer layer> A primer layer 50 may be provided on the hard coat layer 42. Examples of materials constituting the primer layer 50 include metals such as silicon, nickel, chromium, tin, gold, silver, platinum, zinc, titanium, tungsten, aluminum, zirconium, and palladium; alloys of these metals; and oxides, fluorides, sulfides, or nitrides of these metals. Among these, oxides are preferred as the material for the primer layer, and silicon oxide is particularly preferred. Silicon oxide has a small refractive index, so that it can reduce the reflection of visible light at the interface between the transparent film substrate 4 (hard coat layer 42) and the primer layer 50.
[0062] The primer layer 50 is preferably an inorganic oxide layer, and may be an oxide layer having a smaller amount of oxygen than the stoichiometric composition. Among inorganic oxides having a non-stoichiometric composition, silicon oxide represented by the composition formula SiOx (0.5≦x<2) is preferable. In particular, by providing a silicon oxide layer having a non-stoichiometric composition as the primer layer 50 on the hard coat layer 42 containing silica particles as nanoparticles, the primer layer 50 can be firmly adhered to the hard coat layer 42.
[0063] The thickness of the primer layer 50 is, for example, about 1 to 20 nm, preferably 2 to 15 nm, and more preferably 3 to 15 nm. If the thickness of the primer layer is within the above range, both improved adhesion and light transmittance can be achieved.
[0064] <Anti-reflection layer> The antireflection layer 5 is a laminate of multiple thin films with different refractive indices. In general, the optical film thickness (product of refractive index and thickness) of the thin films of the antireflection layer is adjusted so that the inverted phases of incident light and reflected light cancel each other out. A multilayer laminate of multiple thin films with different refractive indices can reduce the reflectance in a wide wavelength range of visible light. Examples of materials for the thin films constituting the antireflection layer 5 include metal oxides, nitrides, and fluorides. The antireflection layer 5 is preferably an alternating laminate of high refractive index layers and low refractive index layers. In order to reduce reflection at the air interface, the thin film 54 provided as the outermost layer of the antireflection layer 5 (the layer farthest from the transparent film substrate 4) is preferably a low refractive index layer.
[0065] The high refractive index layers 51, 53 have a refractive index of, for example, 1.9 or more, preferably 2.0 or more. Examples of high refractive index materials include titanium oxide, niobium oxide, zirconium oxide, tantalum oxide, zinc oxide, indium oxide, indium tin oxide (ITO), and antimony-doped tin oxide (ATO). Among these, titanium oxide or niobium oxide is preferable. The low refractive index layers 52, 54 have a refractive index of, for example, 1.6 or less, preferably 1.5 or less. Examples of low refractive index materials include silicon oxide, titanium nitride, magnesium fluoride, barium fluoride, calcium fluoride, hafnium fluoride, and lanthanum fluoride. Among these, silicon oxide is preferable. In particular, it is preferable to alternately stack niobium oxide (Nb2O5) thin films 51, 53 as high refractive index layers and silicon oxide (SiO2) thin films 52, 54 as low refractive index layers. In addition to the low refractive index layer and the high refractive index layer, a medium refractive index layer having a refractive index of about 1.6 to 1.9 may be provided.
[0066] The thickness of each of the high refractive index layer and the low refractive index layer is about 5 to 200 nm, and preferably about 15 to 150 μm. The thickness of each layer may be designed according to the refractive index, the layer structure, etc., so that the reflectance of visible light is small.
[0067] The method for forming the thin films constituting the primer layer 50 and the anti-reflection layer 5 is not particularly limited, and may be either a wet coating method or a dry coating method. Dry coating methods such as vacuum deposition, CVD, sputtering, and electron beam vapor deposition are preferred because they can form thin films with a uniform thickness. Among these, sputtering is preferred because it has excellent uniformity in thickness.
[0068] <Anti-stain layer> The antireflection film 105 may have an additional functional layer on the antireflection layer 5. For example, an antifouling layer 6 may be provided on the antireflection layer 5 for the purpose of preventing contamination from the external environment and facilitating the removal of attached contaminants.
[0069] When the antifouling layer 6 is provided on the surface of the antireflection film, it is preferable that the difference in refractive index between the low refractive index layer 54 on the outermost surface of the antireflection layer 5 and the antifouling layer is small from the viewpoint of reducing reflection at the interface. The refractive index of the antifouling layer is preferably 1.6 or less, more preferably 1.55 or less. The material of the antifouling layer is preferably a fluorine group-containing silane-based compound, a fluorine group-containing organic compound, or the like. The antifouling layer can be formed by a wet process such as a reverse coating method, a die coating method, or a gravure coating method, or a dry process such as a vacuum deposition method or a CVD method. The thickness of the antifouling layer 6 is usually about 1 to 50 nm, preferably 2 to 30 nm, and more preferably 3 to 20 nm.
[0070] [Polarizing plate with anti-reflection layer] A polarizing plate with an antireflection layer is obtained by bonding a second main surface of an antireflection film 105 to a first main surface (on the barrier layer 3) of the polarizing plate with a barrier layer 101 via an adhesive layer 8.
[0071] A material having a high visible light transmittance is preferably used as the adhesive layer 8. For example, an acrylic adhesive has excellent optical transparency, exhibits appropriate wettability, cohesiveness, and adhesiveness, and is excellent in weather resistance, heat resistance, etc., and is therefore suitable as a material for the adhesive layer 8 used to bond the polarizing plate 101 and the anti-reflection film 105. The thickness of the adhesive layer 8 is generally about 5 to 100 μm, and preferably about 10 to 50 μm.
[0072] In a polarizing plate with an antireflection layer, in which an antireflection film 105 is laminated onto a polarizing plate with a barrier layer 101, the low moisture permeable barrier layer 3 blocks the intrusion of moisture into the polarizer 1, and therefore deterioration of the polarizer 1 caused by moisture in the air can be suppressed. Even if a fine scratch occurs in the antireflection layer 5 provided on the surface, the barrier layer 3 suppresses the intrusion of moisture into the polarizer, so deterioration of the polarizer is unlikely to occur and the polarizer has excellent resistance to moisture and heat. The polarizing plate with an antireflection layer has excellent resistance to moisture and heat when exposed to a high-temperature and high-humidity environment. * It is preferable that the change in is small. * La * b * Chromaticity in color space, chromaticity of transmitted light b *The larger the value, the yellower the transmitted light appears.
[0073] When a polarizer using iodine as a dichroic material is exposed to a high temperature and humidity environment, iodine ions (I3 - and I5 - ) balance is lost, and the transmittance of the visible light short wavelength region decreases, causing yellowing. * Therefore, b * The change in b is an indicator of the deterioration of the polarizer caused by moisture. * The smaller the change in the resistance, the higher the durability.
[0074] The polarizing plate with anti-reflection layer is left in an environment of 65℃ and 90% humidity for 72 hours. * The change in value is preferably 1.5 or less, more preferably 1.3 or less, even more preferably 1.0 or less, and particularly preferably 0.5 or less. The polarizing plate with an antireflection layer has a chromaticity b * The change is preferably 1.8 or less, more preferably 1.5 or less, even more preferably 1.0 or less, and particularly preferably 0.5 or less.
[0075] b * As described above, by forming the barrier layer 3 on the film 2 having a small arithmetic mean height Sa, the moisture permeability of the barrier layer 3 tends to be small, and * In addition, by forming the barrier layer 3 on the film 2 that has a small moisture absorption expansion, cracks are less likely to occur in the barrier layer, and deterioration of the polarizer caused by moisture penetration through the cracks tends to be suppressed.
[0076] The polarizing plate with an antireflection layer has an antireflection layer 5 on its surface, which prevents reflection of external light in an image display device and contributes to improving the visibility of a displayed image. Light incident from the second main surface side is also reflected at interfaces between other layers. In particular, reflection is likely to occur at the interface between the barrier layer 3 and the pressure-sensitive adhesive layer 8 due to the difference in refractive index, so it is preferable to reduce the reflectance at the interface.
[0077] The interface reflectance between the barrier layer 3 and the adhesive layer 8 is preferably 1% or less, more preferably 0.5% or less, further preferably 0.2% or less, and may be 0.15% or less or 0.1% or less. The interface reflectance is the difference Y1-Y0 between the regular reflectance Y1 (%) of the polarizing plate with an antireflection layer, in which the antireflection film 105 is laminated to the surface of the barrier layer 3 of the polarizing plate 101 via the adhesive layer 8, and the regular reflectance Y0 (%) of the antireflection film 105 before being laminated to the polarizing plate. The regular reflectances Y0 and Y1 are Y values obtained by measuring the regular reflection spectrum in a 2-degree field of view using a sample in which a black acrylic plate is laminated to the back surface of the sample via the adhesive layer to eliminate back surface reflection, and then performing luminosity correction from the obtained spectrum.
[0078] [Image display device] The polarizing plate with an anti-reflection layer is used by being disposed on the surface of an image display device such as a liquid crystal display or an organic EL display. For example, the second main surface of the polarizing plate 101 is bonded to an image display medium 110 such as a liquid crystal cell or an organic EL cell via an adhesive layer 9 to form an image display device 300. By disposing the polarizing plate with an anti-reflection layer on the viewing side surface, the reflection of external light can be reduced and the visibility of the image display device can be improved. Since the low moisture permeable barrier layer 3 is provided on the second main surface of the polarizing plate 101, even if the anti-reflection layer 5 is scratched during use of the image display device, it is possible to suppress the intrusion of moisture into the polarizer 1, and an image display device with excellent durability and which is less likely to suffer from deterioration in display characteristics or uneven display caused by deterioration of the polarizer even when exposed to a high temperature and high humidity environment can be obtained. EXAMPLES
[0079] The present invention will be described in more detail below by way of examples, but the present invention is not limited to the following examples.
[0080] [Example 1] <Preparation of polarizing plate> One side of a 100 μm-thick amorphous polyester film (polyethylene terephthalate / isophthalate; glass transition temperature 75°C) was subjected to a corona treatment, and an aqueous solution containing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetoacetyl-modified polyvinyl alcohol (Nippon Synthetic Chemical Industry "Gosefimer Z200"; degree of polymerization 1200, degree of acetoacetyl modification 4.6%, degree of saponification ≥ 99.0 mol%) in a weight ratio of 9:1 was applied to the corona-treated surface and dried at 25°C to produce a laminate in which an 11 μm-thick PVA-based resin layer was provided on the amorphous polyester film substrate.
[0081] This laminate was free-end uniaxially stretched to 2.0 times in the longitudinal direction by air-assisted stretching in an oven at 120 ° C., and then immersed in a 4% boric acid aqueous solution at 30 ° C. for 30 seconds and in a dyeing solution (0.2% iodine, 1.0% potassium iodide aqueous solution) at 30 ° C. for 60 seconds while being transported with a roll. Next, while transporting the laminate with a roll, it was immersed in a crosslinking solution (3% potassium iodide, 3% boric acid aqueous solution) at 30 ° C. for 30 seconds to perform a crosslinking treatment, and while being immersed in a 4% boric acid, 5% potassium iodide aqueous solution at 70 ° C., it was free-end uniaxially stretched to a total stretch ratio of 5.5 times in the longitudinal direction. Thereafter, the laminate was immersed in a cleaning solution (4% potassium iodide aqueous solution) at 30 ° C. to obtain a laminate in which a PVA-based polarizer having a thickness of 5 μm was provided on an amorphous polyester film substrate.
[0082] An ultraviolet-curing adhesive was prepared containing 40 parts by weight of N-hydroxyethylacrylamide and 60 parts by weight of acryloylmorpholine as curable components, and further containing 3 parts by weight of 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (BASF's "Irgacure 819") as a polymerization initiator. This adhesive was applied to the surface of the polarizer of the laminated body in a thickness of about 1 μm, and the non-hard coat layer side of a 40 μm-thick acrylic film having a 3 μm-thick hard coat layer formed on one side was attached thereto, and an integrated light dose of 1000 / mJ / cm was applied. 2 The adhesive was cured by irradiating it with ultraviolet light of 1000 nm. The acrylic film used was one containing an acrylic resin having a lactone ring structure as its main component.
[0083] The amorphous polyester film substrate was peeled off from the laminate, and the above-mentioned active energy ray curable adhesive solution was applied to the surface of the PVA resin layer from which the film substrate was peeled off, and the first retardation layer was laminated thereon, and the above-mentioned active energy ray curable adhesive was further applied thereon to laminate the second retardation layer. The first retardation layer was a biaxially stretched cyclic polyolefin film (negative B plate) with an in-plane retardation of 116 nm, and the second retardation layer was a biaxially stretched modified polyethylene film (positive B plate) with an in-plane retardation of 35 nm, and the lamination was performed so that the slow axis direction of the first retardation layer was parallel to the absorption axis direction of the polarizer, and the slow axis direction of the second retardation layer was perpendicular to the absorption axis direction of the polarizer. In this way, a polarizing plate was obtained in which an acrylic film having a hard coat layer on its surface was laminated to one side of a 5 μm-thick polarizer, and the first retardation layer and the second retardation layer were laminated to the other side of the polarizer.
[0084] (Formation of water vapor barrier layer) The polarizing plate was set in a roll-to-roll magnetron sputtering device, and the hard coat layer-formed surface of the polarizing plate was subjected to plasma treatment while introducing Ar gas. Then, DC magnetron sputtering (input power: 500 W, ultimate vacuum: 1×10 -6 A silicon oxide (SiO x ; x<2) A primer layer (thickness: 3 nm) was formed.
[0085] Next, DC magnetron sputtering (input power: 20 kW, ultimate vacuum: 1×10 -4 A SiO2 layer (thickness: 150 nm, refractive index: 1.46) was formed using a sputtering pressure of 0.10 Pa, sputtering gas: O2 / Ar=2 / 1, sputtering pressure: 0.10 Pa, and substrate temperature: -40°C.
[0086] <Preparation of anti-reflection film> (Preparation of hard coat film) An organosilica sol (Nissan Chemical's MEK-ST-L, average primary particle diameter of silica particles: 50 nm, solid content 30% by weight) was added to and mixed with an ultraviolet-curable acrylic resin composition (manufactured by DIC, product name "GSANDIC PC-1070") so that the amount of silica particles was 25 parts by weight relative to 100 parts by weight of the resin component, to prepare a composition for forming a hard coat layer. This composition was applied to one side of a 100 μm-thick triacetyl cellulose film so that the thickness after drying was 3 μm, and dried at 80° C. for 3 minutes. Then, a high-pressure mercury lamp was used to illuminate the film with an accumulated light amount of 200 mJ / cm. 2 The coating layer was cured by irradiation with ultraviolet light of 1000 ohms to form a hard coat layer.
[0087] (Formation of primer layer and anti-reflection layer) The hard coat film after plasma treatment was introduced into a roll-to-roll sputtering deposition device, and the inside of the chamber was heated to 1×10 -4 After reducing the pressure to 10 Pa, the film was run while a substrate temperature of 40°C was maintained and a 10 nm silicon oxide primer layer, a 16 nm Nb2O5 layer, a 19 nm SiO2 layer, a 102 nm Nb2O5 layer and a 71 nm SiO2 layer were formed in that order on the hard coat layer surface to produce an anti-reflection film.
[0088] To deposit the primer layer, a pure Si target was used, and sputtering was performed under the following conditions: input power: 500 W, sputtering gas: Ar, and sputtering pressure: 0.5 Pa. To deposit the Nb2O5 layer, a Nb target was used, and sputtering was performed under the following conditions: input power: 30 kW, sputtering pressure: 0.5 Pa. To deposit the SiO2 layer, a Si target was used, and sputtering was performed under the following conditions: input power: 20 kW, sputtering pressure: 0.5 Pa. To deposit the Nb2O5 layer and SiO2 layer, argon and oxygen were used as sputtering gases, and the amount of oxygen introduced was adjusted using plasma emission monitoring (PEM) control to maintain the deposition mode in the transition region.
[0089] (Formation of antifouling layer) A fluorine-based resin solution containing a perfluoroether structure was applied to the surface of the antireflection layer so as to have a thickness of 9 nm after drying, to form an antifouling layer as a top coat layer.
[0090] <Lamination of polarizing plate and anti-reflection film> A 20 μm thick acrylic transparent adhesive layer was laminated on the film substrate (non-antireflection layer side) of the above antireflection film to prepare an antireflection film with adhesive. The adhesive layer of this antireflection film with adhesive was attached to the barrier layer of a polarizing plate to laminate the polarizing plate and the antireflection film.
[0091] [Example 2] In the preparation of the polarizing plate, a 40 μm thick polycarbonate (PC) film with a 2 μm hard coat layer was used as the polarizer protective film instead of the acrylic film, and a polycarbonate film with a hard coat layer on its surface was attached to one side of a 5 μm thick polarizer, and a first retardation layer and a second retardation layer were attached to the other side of the polarizer to obtain a polarizing plate. A polarizing plate was prepared in the same manner as in Example 1, except that the polarizer protective film on the barrier layer formation surface was changed, and an antireflection film was attached to the surface of the barrier layer of the polarizing plate via an adhesive layer to prepare a polarizing plate with an antireflection layer.
[0092] [Example 3] In the preparation of the polarizing plate, a cyclic polyolefin (COP) film having a thickness of 40 μm was used as the polarizer protective film instead of the acrylic film, and a polarizing plate was obtained in which the cyclic polyolefin film was attached to one surface of a 5 μm-thick polarizer, and the first retardation layer and the second retardation layer were attached to the other surface of the polarizer. A polarizing plate was prepared in the same manner as in Example 1, except that the polarizer protective film on the barrier layer-forming surface was changed.
[0093] The polarizing plate was set in a roll-to-roll magnetron sputtering device, and plasma treatment and formation of a SiOx primer layer were carried out in the same manner as in Example 1. Thereafter, DC magnetron sputtering (input power: 20 kW, ultimate vacuum: 1×10 -4 A SiON2 layer (thickness: 130 nm, refractive index: 1.65) was formed using a sputtering gas of O2 / Ar / N2=3 / 3 / 1, sputtering pressure: 0.10 Pa, and substrate temperature: 40°C. Then, a SiO2 layer (thickness: 20 nm) was formed on the SiON2 layer in the same manner as in Example 1.
[0094] A polarizing plate was prepared in the same manner as in Example 1, except that the polarizer protective film and the barrier layer were changed. An antireflection film was attached to the surface of the barrier layer of the polarizing plate via an adhesive layer to prepare a polarizing plate with an antireflection layer.
[0095] [Example 4] A polarizing plate similar to that in Example 1 was used, and the surface on which the hard coat layer was formed was subjected to plasma treatment in the same manner as in Example 1. Then, DC magnetron sputtering (input power: 20 kW, ultimate vacuum: 1×10) was performed using targets containing ZnO, Al, and SiO. -4 A composite oxide layer (thickness: 120 nm, refractive index: 1.65) was formed using a sputtering pressure of 0.10 Pa, sputtering gas: O2 / Ar=5 / 100, sputtering pressure: 0.10 Pa, and substrate temperature: 40°C. Then, a SiO2 layer (thickness: 85 nm) was formed using the same method as in Example 1.
[0096] [Comparative Example 1] A polarizing plate was prepared in the same manner as in Example 1, except that no barrier layer was provided on the surface of the polarizing plate. An antireflection film was attached to the hard coat layer on the acrylic polarizer protective film of the polarizing plate via an adhesive layer, thereby preparing a polarizing plate with an antireflection layer.
[0097] [Comparative Example 2] In the formation of the Nb2O5 layer and SiO2 layer of the antireflection film, the argon flow rate was reduced, and the film formation was performed at a sputtering pressure of 0.1 Pa to prepare a low-moisture permeable antireflection film. Otherwise, in the same manner as in Comparative Example 1, a low-moisture permeable antireflection film was attached via an adhesive layer onto the hard coat layer on the acrylic polarizer protective film of the polarizing plate, to prepare a polarizing plate with an antireflection layer.
[0098] [Comparative Example 3] In the preparation of the polarizing plate, a 40 μm-thick triacetyl cellulose (TAC) film with a 2 μm-thick hard coat layer was used as the polarizer protective film instead of the acrylic film, and a polarizing plate was obtained in which a TAC film with a hard coat layer on its surface was attached to one side of a 5 μm-thick polarizer, and a first retardation layer and a second retardation layer were attached to the other side of the polarizer. A polarizing plate was prepared in the same manner as in Example 1, except that the polarizer protective film on the barrier layer formation side was changed, and an antireflection film was attached to the surface of the barrier layer of the polarizing plate via an adhesive layer, to prepare a polarizing plate with an antireflection layer.
[0099] [Comparative Example 4] A polarizing plate with an antireflection layer was produced in the same manner as in Comparative Example 3, except that the polarizer protective film on the barrier layer forming surface was changed to a TAC film not provided with a hard coat layer.
[0100] [Comparative Example 5] A polarizing plate with an antireflection layer was produced in the same manner as in Example 1 except that the polarizer protective film on the barrier layer forming surface was changed to an acrylic film not provided with a hard coat layer.
[0101] [evaluation] <Arithmetic mean roughness Sa of transparent protective film> The polarizer protective film before being bonded to the polarizer, and the polarizing plate after plasma treatment (before the barrier layer was formed) were used as samples. Using an atomic force microscope (AFM) under the conditions below, the three-dimensional surface shapes of the barrier layer-formed surface (the surface opposite the surface bonded to the polarizer) before and after the plasma treatment were measured, and the arithmetic average surface roughness Sa was measured in accordance with ISO 25178. Device: Bruker "Dimemsion3100", Controller: NanoscopeV Measurement mode: Tapping mode Cantilever: Si single crystal Measurement field of view: 1μm×1μm
[0102] <Moisture permeability> The moisture permeability of the barrier layer and anti-reflection film was measured at a temperature of 40°C and a relative humidity difference of 90% according to JIS K 7129:2008, Appendix B (Mocon method). The polarizing plates prepared in each of the Examples and Comparative Examples were used to measure the moisture permeability of the barrier layer. Note that since the moisture permeability of the barrier layer was sufficiently smaller than that of the polarizing plate, the moisture permeability of the sample in which the barrier layer was formed on the polarizing plate was regarded as the moisture permeability of the barrier layer.
[0103] <Moisture absorption expansion rate> A square test piece of 100 mm x 100 mm was cut out from the polarizer protective film before bonding with the polarizer, and was left to stand for 48 hours under conditions of 23 ° C. temperature and 65% RH relative humidity to adjust the condition, and then four marks (scratches) were formed at 80 mm intervals in the MD direction (the conveying direction during roll conveying) and TD direction (the direction perpendicular to the MD direction), and the distance L0 between the marks was measured using a surface coordinate measuring machine (TOPCON "CP600S"). After standing for 72 hours in a thermo-hygrostat chamber at a temperature of 65 ° C. and a relative humidity of 90%, it was allowed to cool to room temperature under conditions of 23 ° C. temperature and 65% RH relative humidity, and the distance L between the marks was measured. The average of the thermal dimensional change rates at two points for each of the MD and TD was taken as the hygroscopic expansion coefficient. The sign + of the hygroscopic expansion coefficient indicates expansion, and the sign - indicates shrinkage.
[0104] <Single transmittance of polarizing plate with anti-reflection film> The transmittance of the polarizing plate with anti-reflection film was measured by irradiating light from the polarizing plate side using a spectral transmittance meter with an integrating sphere (Murakami Color Research Laboratory's "DOT-3C"). The transmittance value is the Y value corrected for visibility using a 2-degree visual field (C light source) according to JIS Z8701, with completely polarized light obtained through a Glan-Teller prism being taken as 100%.
[0105] <Interface reflectance> A 2 mm thick black acrylic plate (manufactured by Mitsubishi Chemical) was attached to the polarizing plate side of the anti-reflection film-attached polarizing plate via a transparent acrylic adhesive. The sample was irradiated with light from a D65 light source from the anti-reflection film side, and a 2-degree visual field regular reflection spectrum was measured using a spectrophotometer (Konica Minolta "CM2600d"), and the reflection Y value (Y1) was calculated from the obtained spectrum. The reflection Y value (Y0) was similarly calculated for a sample in which a 2 mm thick black acrylic plate was attached to the transparent film side of the anti-reflection film before being attached to the polarizing plate via a transparent acrylic adhesive. The difference Y1-Y0 between the regular reflectance Y1 of the polarizing plate with the anti-reflection film and the regular reflectance Y0 of the anti-reflection film was taken as the reflectance of the surface of the polarizing plate (or the interface of the barrier layer if a barrier layer is provided).
[0106] <High temperature and humidity durability test of polarizing plate with anti-reflection layer> (Sample Preparation) The polarizing plate with anti-reflection layer was cut into a size of 5 cm in MD × 10 cm in TD, and the surface of the polarizing plate side was attached to a glass plate via a transparent acrylic adhesive. A load of 300 g was applied to the surface (anti-reflection layer) of this sample with #1200 sandpaper (25 mmφ) and it was moved back and forth once in the TD direction for a length of 5 cm to scratch the anti-reflection layer, and the right half of the sample was designated as the "scratched area" and the left half was designated as the "non-scratched area".
[0107] (hue change) Using a spectral transmittance meter with an integrating sphere (Murakami Color Research Laboratory's "DOT-3C"), light was incident from the polarizing plate side (glass plate side) and the chromaticity b of the transmitted light of the polarizing plate with anti-reflection film was measured. *The sample was then placed in a thermohygrostat at 65°C and 90% relative humidity for 72 hours and cooled to room temperature. * 1 and measure the b before and after the high temperature and high humidity durability test. * The change in Δb * =b * 1-b * The result was 0.
[0108] (Mura) The sample after the high temperature and high humidity durability test was placed on a tracing table, and the presence or absence of color unevenness around the scratches in the scratched areas was visually confirmed, and evaluated according to the following criteria. 〇: No yellowing or unevenness is observed △: The whole surface is yellowed and no unevenness can be confirmed. ×: Clear unevenness is observed around the scratches
[0109] The scratch-free areas of the samples after the high-temperature, high-humidity durability test were observed under an optical microscope (objective lens: 20x) in a 600 μm × 500 μm field of view to check for the presence or absence of cracks in the barrier layer. Those without cracks were marked with "◯" and those with cracks were marked with "X".
[0110] [Evaluation Results] Table 1 shows the configurations and evaluation results of the polarizing plates with an antireflection layer of the above examples and comparative examples.
[0111] [Table 1]
[0112] In Comparative Example 1, in which an anti-reflection film was laminated onto a polarizer protective film without providing a barrier layer, after a high-temperature and high-humidity durability test, both the scratched and non-scratched areas showed a * In Comparative Example 2, in which a low moisture permeable anti-reflection film was laminated onto a polarizer protective film without providing a barrier layer, good durability was exhibited in the scratch-free area, but in the scratched area, after the high temperature and high humidity durability test, *There was an increase in.
[0113] From these results, it can be seen that in Comparative Example 1, the anti-reflection layer does not provide a sufficient water vapor barrier effect, and therefore the polarizing plate turns yellow when exposed to a high-temperature and high-humidity environment. * In Comparative Example 2, since the antireflection layer has low moisture permeability, when the antireflection layer is not scratched, it shows excellent durability. However, when the antireflection layer is scratched, moisture penetrates through the scratch, causing the polarizer to yellow, resulting in a decrease in the resistance to moisture. * is thought to have increased.
[0114] In Examples 1 to 4 in which a barrier layer was provided on the polarizer protective film and an anti-reflection film was attached thereon, the b * It can be seen that the change in is small, indicating excellent durability.
[0115] In Comparative Example 3, although a barrier layer similar to that in Example 1 was provided on the TAC film as the polarizer protective film, after the high temperature and high humidity durability test, * In Comparative Example 3, cracks were generated in the barrier layer after the high temperature and high humidity durability test. A similar tendency was observed in Comparative Example 4, in which a TAC film without a hard layer was used as the polarizer protective film. In Comparative Examples 3 and 4, the dimensional change of the film that serves as the base for the formation of the barrier layer was large, so that cracks were generated in the barrier layer and the water vapor barrier property could not be ensured, which is considered to be the cause of the yellowing and unevenness of the polarizing plate.
[0116] In Comparative Example 5, in which a barrier layer was provided on an acrylic film not provided with a hard coat layer, the moisture permeability of the barrier layer was lower than that of Example 1, and the high-temperature, high-humidity durability of the polarizing plate with an antireflection layer was also lower, even though the material and thickness of the thin film constituting the barrier layer were the same. Note that in Example 3, the moisture permeability of the barrier layer was low even though a hard coat layer was not provided on the COP film serving as a polarizer protective film, so it is believed that the presence or absence of a hard coat layer does not directly affect the moisture permeability of the barrier layer, but rather that in Example 1, the surface roughness Sa was reduced by providing a hard coat layer, and the moisture permeability was reduced by providing a barrier layer thereon in Example 1, thereby improving the durability of the polarizing plate.
[0117] A comparison between Comparative Example 1 and Example 4 shows that when a barrier layer is provided, the reflectance at the surface of the polarizing plate tends to be high. On the other hand, a comparison between Example 4 and Example 1 shows that by adjusting the layer stacking configuration of the barrier layer, it is possible to reduce the reflectance at the interface and achieve excellent visibility even when a barrier layer is provided. [Explanation of symbols]
[0118] 300 Image display device 200 Polarizing plate with anti-reflection layer 101 Polarizing plate with barrier layer 1 Polarizer 2 Transparent protective film 21 Transparent Film 22 Coating layer (smoothing layer) 3. Water Vapor Barrier Layer 15 Polarizer protection film 105 Anti-reflective film 4 Transparent film substrate 41 Transparent Film 42 Hard coat layer 50 primer layer 5 Anti-reflection layer 51,53 Low refractive index layer 52,54 High refractive index layer 6. Antifouling layer 8,9 Adhesive layer 110 Image display media
Claims
1. A polarizing plate with an antireflection layer, in which a polarizing plate and an antireflection film are laminated, a polarizing plate comprising a polarizer, a first transparent protective film bonded to a first main surface of the polarizer, and a water vapor barrier layer provided on the first main surface of the first transparent protective film; An antireflection film comprising a transparent film substrate and an antireflection layer provided on a first main surface of the transparent film substrate; and a pressure-sensitive adhesive layer disposed between the polarizing plate and the antireflection film; Equipped with the water vapor barrier layer of the polarizing plate and the second main surface of the transparent film substrate are bonded to each other via the pressure-sensitive adhesive layer, The first transparent protective film has a moisture swelling coefficient of 0.10% or less, The arithmetic mean height Sa of the first main surface of the first transparent protective film is 1.5 nm or less, The moisture permeability of the water vapor barrier layer is 1 g / m 2 - 24 hours or less, Polarizer with anti-reflective layer.
2. 2. The polarizing plate with an antireflection layer according to claim 1, wherein the water vapor barrier layer is a ceramic layer containing an oxide, nitride or oxynitride of one or more elements selected from the group consisting of Si, Al, In, Sn, Zn, Ti, Nb, Ce and Zr.
3. The polarizing plate with an antireflection layer according to claim 2 , wherein the water vapor barrier layer is a sputtered film.
4. The polarizing plate with an antireflection layer according to any one of claims 1 to 3, wherein the first transparent protective film has a smoothing coating layer on a first main surface of the transparent film.
5. 5. The polarizing plate with an antireflection layer according to claim 1, further comprising a second transparent protective film attached to a second main surface of the polarizer.
6. 6. The polarizing plate with an antireflection layer according to claim 1, wherein the interface reflectance between the water vapor barrier layer and the pressure-sensitive adhesive layer is 1% or less.
7. 7. The polarizing plate with an antireflection layer according to claim 1, wherein the antireflection layer is a laminate of a plurality of thin films having different refractive indices.
8. 8. The polarizing plate with an antireflection layer according to claim 1, wherein the antireflection layer is a sputtered film.
9. 9. The polarizing plate with an antireflection layer according to claim 1, wherein the antireflection film comprises an antifouling layer on the antireflection layer.
10. 10. The polarizing plate with an antireflection layer according to claim 1, wherein the antireflection film comprises a primer layer between the transparent film substrate and the antireflection layer.
11. The polarizing plate with an antireflection layer according to any one of claims 1 to 10, wherein the transparent film substrate has a hard coat layer on a first main surface of the transparent film.
12. 12. An image display device, comprising: an image display medium; and a polarizing plate with an antireflection layer according to claim 1 disposed on a viewing side surface of the image display medium.
Citation Information
Patent Citations
Protection film for polarizing plate, polarizing plate, and liquid crystal display device
JP2006292834A
Polarizing plate with adhesive
JP2010231160A
Antireflection film
JP2011069995A
Polarizing film with adhesive layer, and image display device
JP2015106150A
Optical laminate
JP2017134370A